The γ-Glutamyl Cycle in the Choroid Plexus: Its Possible Function in Amino Acid Transport - Tate, Suresh S. (1973)
Various anatomic regions of rabbit brain have been examined for activities of the enzymes of the γ-glutamyl cycle. While these enzyme activities were widely distributed in the brain, they are present in much higher concentrations in the choroid plexus than in other parts of the brain. The activities observed are of about the same order of magnitude as found in the kidney. These observations and other considerations suggest that the γ-glutamyl cycle may play a significant role in the transport of amino acids between blood and cerebrospinal fluid.